Acute toxicity of combined photon IMRT and carbon ion boost for intermediate-risk prostate cancer: acute toxicity of 12C for PC - Nikoghosyan, Anna; Schulz-Ertner, Daniela; Herfarth, Klaus; Didinger, Bernd Herbert; Münter, Marc; Jensen, Alexandra; Jäkel, Oliver; Höss, Angelika; Haberer, Thomas; Debus, Jürgen (Acta oncologica, 2011)
Background. Carbon ion (12C) therapy in the treatment of prostate cancer (PC) might result in an improved outcome as compared to low linear energy transfer irradiation techniques. In this study, we present the first interim report of acute side effects of the first intermediate-risk PC patients treated at the GSI (Gesellschaft für Schwerionenforschung) and the University of Heidelberg in an ongoing clinical phase I/II trial using combined photon intensity modulated radiation therapy (IMRT) and 12C carbon ion boost. Material and methods. Fourteen patients (planned accrual: 31 pts) have been treated within this trial so far. IMRT is prescribed to the median PTV at a dose of 30 × 2 Gy; 12C boost is applied to the prostate (GTV) at a dose of 6 × 3 GyE using raster scan technique. Safety margins added to the clinical target volume were determined individually for each patient based on five independent planning computed tomography (CT)-scans. Acute gastrointestinal (GI) and genitourinary (GU) toxicity was assessed and documented according to the CTCAE Version 3.0. Results. Radiotherapy was very well tolerated without any grade 3 or higher toxicity. Acute anal bleeding grade 2 was observed in 2/14 patients. Rectal tenesmus grade 1 was reported by three other patients. No further GI symptoms have been observed. Most common acute symptoms during radiotherapy were nocturia and dysuria CTC grade 1 and 2 (12/14). There was no severe acute GU toxicity. Conclusion. The combination of photon IMRT and carbon ion boost is feasible in patients with intermediate-risk PC. So far, the treatment has been well tolerated. Acute toxicity rates were in good accordance with data reported for high dose IMRT alone.
Gesehen am 28.09.2022